Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1287/mnsc.2017.2901
|View full text |Cite
|
Sign up to set email alerts
|

Awareness Reduces Racial Bias

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
73
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(76 citation statements)
references
References 23 publications
(7 reference statements)
3
73
0
Order By: Relevance
“…However, this is difficult in sport given the public nature in which all participants, in particular the referees, operate. Given that referees have shown a willingness to adapt their behavior when made aware of their biases (Pope, Price, and Wolfers 2013), one solution may simply be to make the league aware of this behavior. Ultimately, however, unless team personnel are removed from direct contact with the run of play, it may be impossible to remove a sideline bias from the NFL.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this is difficult in sport given the public nature in which all participants, in particular the referees, operate. Given that referees have shown a willingness to adapt their behavior when made aware of their biases (Pope, Price, and Wolfers 2013), one solution may simply be to make the league aware of this behavior. Ultimately, however, unless team personnel are removed from direct contact with the run of play, it may be impossible to remove a sideline bias from the NFL.…”
Section: Discussionmentioning
confidence: 99%
“…Other social pressures on referees, including whether or not the contest is on television (Lane et al 2006), and the choice to make fewer calls at game's end so as to avoid being part of a game's narrative (Moskowitz and Wertheim 2011;Snyder and Lopez 2015), have also been suggested. And although their behavior is susceptible to outside factors, the monitoring of referees has been shown to reduce bias (Parsons et al 2011;Pope, Price, and Wolfers 2013). One aspect missing in the literature, but a part of the flow of any athletic event, is accounting for the pressure and monitoring applied on referees by team employees.…”
Section: Introductionmentioning
confidence: 99%
“…This explanation is based on the notion that awareness can reduce one's subconscious biases. Racial bias in professional basketball referees persisted even after a study showed such bias [26], but disappeared after extensive media coverage of that study, suggesting that awareness reduced such bias [24]. Making crowdworkers aware of their own biases reduced their own biases [14], and academic promotion committees in scientific fields do not promote more men over women when they believe that gender bias exists [28].…”
Section: Potential Interpretationsmentioning
confidence: 95%
“…The first goal would be to expose judges to findings concerning the effects of legally relevant and legally irrelevant factors on decisions, with the goal of general rather than specific debiasing. For example, Pope, Price, and Wolfers (2013) found that awareness of racial bias among NBA referees subsequently reduced that bias. The second goal would be to educate legal decision makers in the tools of data analysis, so that they can become better consumers of this information when it is present during legal proceedings, and to more generally provide a set of thinking tools for understanding inference, prediction, and the conscious and unconscious factors that may influence their decision making.…”
Section: Judicial Educationmentioning
confidence: 99%